STRUKTUR DAN BENTUK GENDING TARI HANDAGA BUGIS DI PURA MANGKUNEGARAN - Indah Ayu Saputri (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
The Handaga Bugis dance at Mangkunegaran Temple is a wireng genre dance. The presentation of this dance cannot be separated from the musical accompaniment as one of the determining factors for the success of the performance both in welcoming guests at the Mangkunegaran Temple and in a festival. This study aims to describe the structure and form of music in the Handaga Bugis dance performance at Mangkunegaran Temple. Qualitative research methods with observation and interview techniques are used to support the data collection process in this study. In its presentation, this dance has standard music/accompaniment (standard) as a form of wireng dance. The forms of gending used are sampak sanga, lancaran kandhang bubrah pelog pathet nem, ketawang puspanjala pelog pathet nem, kemudha pelog pathet nem, ayak-ayak sanga wiled. Based on the structure, several gending have similarities and differences in the level of rhythm, beat and execution.